PBK promotes aggressive phenotypes of cervical cancer through ERK/c‐Myc signaling pathway. Issue 4 (13th November 2020) - Ma, Hanlin; Han, Fang; Yan, Xiaohui; Qi, Gonghua; Li, Yingwei; Li, Rongrong; Yan, Shi; Yuan, Cunzhong; Song, Kun; Kong, Beihua
Abstract: Cervical cancer is the fourth most frequent cancer in women worldwide. PDZ‐binding kinase (PBK) is proven to promote the malignant behaviors of various carcinomas. However, its functional roles and oncogenic mechanisms in cervical cancer are poorly understood. In this study, we reported that PBK was highly expressed in cervical cancer tissues. PBK promoted the proliferation, metastasis, and cisplatin resistance of cervical cancer cells. OTS514, a specific PBK inhibitor, could significantly suppress proliferation and metastasis of cervical cancer cells in vitro and in a xenograft model. Besides, OTS514 could enhance cisplatin‐based chemosensitivity in cervical cancer cells. Mechanistically, PBK promoted the expression and stabilization of c‐Myc through phosphorylating ERK1/2. OTS514 suppressed the phosphorylation of ERK1/2 and the transcriptional activity of c‐Myc. Furthermore, inhibition of the ERK signal pathway by U0126 reversed the increased proliferation and metastasis induced by overexpression of PBK. Exogenous expression of c‐Myc counteracted the decreased proliferation and metastasis evoked by knockdown of PBK. In conclusion, PBK promoted the malignant progression of cervical cancer through ERK/c‐Myc signal pathway. PBK might be a promising molecular target for cervical cancer treatment. Abstract : PDZ‐binding kinase (PBK) promoted the malignant progression of cervical cancer through ERK/c‐Myc signal pathway. PBK might be a promising molecular target for cervical cancer treatment.